(untitled) - Keene, Carolyn; Pamintuan, Macky (New York, 2008)
When Nancy and her friends are going to be in a ballet version of Cinderella and the special glass slippers go missing, Nancy is determined to find them before show time.
Reprint. Originally published: 2006.
Keywords: Fiction; Fiction; Lost and found possessions; Ballet; Fiction; Juvenile fiction